Logic and modality - Bevan, M (2022)
In this thesis I consider and argue against various versions of the view that logical truth and necessity are identical. I criticise purely modalist accounts of logical consequence, according to which consequence is just necessary truth-preservation, and I also criticise views on which necessity is identified with some prior understanding of logical truth (as semantic validity, or substitutional validity, or as syntactic derivability). In the process I develop various systems of modal semantics in detail and investigate the logic of logical truth under various alternative hypotheses.